2001
DOI: 10.1152/ajplung.2001.280.2.l221
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Ca2+signaling in alveolar epithelial cells through gap junctions and by extracellular ATP

Abstract: Inter- and extracellular-mediated changes in intracellular Ca2+ concentration ([Ca2+]i) can ensure coordinated tissue function in the lung. Cultured rat alveolar epithelial cells (AECs) have been shown to respond to secretagogues with increases in [Ca2+]i and have been shown to be gap junctionally coupled. However, communication of [Ca2+]i changes in AECs is not well defined. Monolayers of AECs were mechanically perturbed and monitored for [Ca2+]i changes. Perturbation of AECs was administered by a glass probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 53 publications
6
80
0
Order By: Relevance
“…However, the recent availability of the connexin-mimetic peptides gap26 and gap27 provides a suitable alternative to the traditional pharmacological inhibitors (15)(16)(17). These peptides, respectively, bind the sequences VCYDKSFPISHVR and SRPTEKTIFII in extracellular loops 1 and 2 of Cx43 (15,17), blocking gap junctional communication in several cell types (11,15,32). Although the mechanisms are unclear, it is suggested that the peptides inhibit cell communication by either gating or disrupting gap junction channels (11,33,34).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…However, the recent availability of the connexin-mimetic peptides gap26 and gap27 provides a suitable alternative to the traditional pharmacological inhibitors (15)(16)(17). These peptides, respectively, bind the sequences VCYDKSFPISHVR and SRPTEKTIFII in extracellular loops 1 and 2 of Cx43 (15,17), blocking gap junctional communication in several cell types (11,15,32). Although the mechanisms are unclear, it is suggested that the peptides inhibit cell communication by either gating or disrupting gap junction channels (11,33,34).…”
Section: Figurementioning
confidence: 99%
“…These peptides, respectively, bind the sequences VCYDKSFPISHVR and SRPTEKTIFII in extracellular loops 1 and 2 of Cx43 (15,17), blocking gap junctional communication in several cell types (11,15,32). Although the mechanisms are unclear, it is suggested that the peptides inhibit cell communication by either gating or disrupting gap junction channels (11,33,34). Attractive features of the gap approach are that the inhibitory effect is reversible and that the mechanistic role of the specific connexin is identified.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Along with the work in [29][30][31][32], this manuscript highlights the role of Cx43 in mediating calcium waves. The paper shows that Cx43-made gap junctions contribute to endothelial cell expression of adhesion molecules for leukocytes.…”
mentioning
confidence: 87%
“…Type I epithelial cells, which represent 90% of alveolar cells and are more subjected to mechanical stress, promote the release of surfactants by type II cells through calcium waves propagation via gap junctions ( Figure 2B) [14,29]. It is important to note that transmission of calcium waves from type I to type II cells can also occur via paracrine stimulation of purinergic receptors through ATP release [30,31]. These calcium signals may also help to adjust surfactant production to stimuli such as changes in pulmonary blood pressure [32,33].…”
Section: Functions Of Connexins In Lungmentioning
confidence: 99%